Developing Complex Network Simulation of Forest Network Spatial Pattern in Pearl River Delta - Yuhuai Zeng (Research Advances in Environment, Geography and Earth Science Vol. 6, 2024)
In the history of more than 2000 years of development, the original forest of the Pearl River Delta area was almost cut down, hilly low mountain area was secondary or sparse forest; Now, Plain water network area grown mulberry, tropical fruit lychee, longan, sugar cane and banana. Vegetation ecological function in the area is weak as the beach, and wetland-based water ecological services are the main components. Forest network construction uses the method and model with the scale-free features of complex network theory based on random graph theory and dynamic network nodes which show a power-law distribution phenomenon. The model is suitable for ecological disturbance by larger ecological landscape Pearl River Delta consistent recovery. Remote sensing and GIS spatial data are available through the latest forest patches. A standard scale-free network node distribution model calculates the area of the forest network’s power-law distribution parameter value size; The recent existing forest polygons which are defined as nodes can compute the network nodes’ decaying index value of the network’s degree distribution. The parameters of the forest network are picked up then make a spatial transition to GIS real world models. Hence the connection is automatically generated by minimizing the ecological corridor by the least cost rule between the near nodes. Based on scale-free network node distribution requirements, select the number compared with less, a huge point of aggregation as a future forest planning network’s main node, and put them with the existing node sequence comparison. By this theory, the forest ecological projects in the past avoid being fragmented, scattered disorderly phenomena. The previous regular forest networks can be reduced the required forest planting costs by this method. For ecological restoration of tropical and subtropical in south China areas, it will provide an effective method for the forest entering city project guidance and demonstration with other ecological networks (water, climate network, etc.) for networking a standard and base datum.